2021
DOI: 10.1002/aenm.202003877
|View full text |Cite
|
Sign up to set email alerts
|

Layered Perovskites in Solar Cells: Structure, Optoelectronic Properties, and Device Design

Abstract: optoelectronic properties akin to industrial juggernauts gallium arsenide and silicon. [1,2] Yet, the materials are compatible with solution-processing techniques such as inkjet printing and spray coating. [3] This unprecedented combination has led to the development of solar cells which already show power conversion efficiencies of over 25%, similar to state-of-the-art poly-Si and other thin-film technologies, in just over 10 years of development. [4] Hybrid perovskites are particularly interesting for indoor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 263 publications
0
59
0
Order By: Relevance
“…Unlike the 3D perovskite with an interconnected structure, 2D perovskite features a layered structure, in which the extended inorganic networks of [PbX 6 ] 4– octahedrons are separated by bulky organic ammonium cations. Because of the significant van der Waals interaction between the well-aligned bulky organic cations, the organic layer could exhibit good thermal resistance. Besides, the hydrophobic organic layer can delay or prevent the direct exposure of the inorganic layer to moisture.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Unlike the 3D perovskite with an interconnected structure, 2D perovskite features a layered structure, in which the extended inorganic networks of [PbX 6 ] 4– octahedrons are separated by bulky organic ammonium cations. Because of the significant van der Waals interaction between the well-aligned bulky organic cations, the organic layer could exhibit good thermal resistance. Besides, the hydrophobic organic layer can delay or prevent the direct exposure of the inorganic layer to moisture.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the hydrophobic organic layer can delay or prevent the direct exposure of the inorganic layer to moisture. Hence, 2D perovskite also displays good moisture stability, which can be further enhanced by reducing the number ( n ) of moisture-sensitive inorganic layers to 1. , To take the advantage of both 2D and 3D perovskites, a variety of 2D/3D hybrid structures have been designed and prepared for PSCs, in which the 2D phase acts as a protective shell against moisture. Nevertheless, it was found that the layered structure of 2D perovskite is not good for out-of-plane carrier transport. As a result, the 2D/3D structure in regular (n–i–p) PSCs may result in blocked hole transfer from the 3D perovskite absorber to the hole transport layer (HTL).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations